2005
DOI: 10.1128/aem.71.8.4713-4720.2005
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Phenylacetaldehyde Reductase for Efficient Substrate Conversion in Concentrated 2-Propanol

Abstract: Phenylacetaldehyde reductase (PAR) is suitable for the conversion of various aryl ketones and 2-alkanones to corresponding chiral alcohols. 2-Propanol acts as a substrate solvent and hydrogen donor of coupled cofactor regeneration during the conversion of substrates catalyzed by PAR. To improve the conversion efficiency in high concentrations of substrate and 2-propanol, selection of a PAR mutant library and the subsequent rearrangement of mutations were attempted. With only a single selection round and follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…was mutated to improve the conversion efficiency in high concentrations of substrate and 2-propanol. 34 Here, 2-propanol acts as a solvent and hydrogen donor of coupled cofactor regeneration during the conversion of substrates. First, the PAR library was generated by mutagenic PCR.…”
Section: Random Followed By Rational Mutations To Improve Catalytic Ementioning
confidence: 99%
“…was mutated to improve the conversion efficiency in high concentrations of substrate and 2-propanol. 34 Here, 2-propanol acts as a solvent and hydrogen donor of coupled cofactor regeneration during the conversion of substrates. First, the PAR library was generated by mutagenic PCR.…”
Section: Random Followed By Rational Mutations To Improve Catalytic Ementioning
confidence: 99%
“…During the analysis of these HPARs, we found that amino acid substitutions within them are scattered but located in quite limited sequence positions. Some of these substitutions completely coincided with those of Sar268 and Har1, which were previously engineered from PAR through application of directed evolution molecular techniques . By analyzing the properties of HPARs and comparing their amino acid sequences, we inferred the relationships between each HPAR amino acid sequence and its properties.…”
mentioning
confidence: 79%
“…E. coli JM109 cells were used to host par genes fused with the pSar268‐del‐fus plasmid. This vector was derived from pSar268 , which expresses the Sar268 ( par mutant) of pUC118, by partial deletion of the Sar268 gene with Kpn I and introduction of a Not I site. To introduce fusion sites to both 5′ ends of this plasmid, PCR was performed using KOD FX DNA polymerase (Toyobo, Osaka, Japan) and the following primers: PAR‐091015 sense, 5′‐CGGGCGCGCGGTTGT‐3′ and PAR‐091015 antisense, 5′‐CCTGGCCCGGGCTC‐3′ (the underlined sequences indicate the fusion sites).…”
Section: Methodsmentioning
confidence: 99%
“…1). 14,15,17) In this report, we describe the cloning, sequence analysis, and expression in Escherichia coli of the gene encoding LSADH from Leifsonia sp. S749, and the purification of the recombinant enzyme.…”
mentioning
confidence: 99%
“…strain ST-10 is a unique NADH-dependent alcohol dehydrogenase (ADH) with a broad substrate range and high enantioselectivity to give (S)-form alcohols without an additional coenzyme regeneration system, because the enzyme itself is able to regenerate NADH in the presence of 2-propanol. [12][13][14] Therefore, a recombinant PAR or its mutated enzyme (Sar268) system 15) and chemotolerant ADH reported in the R. ruber DSM44541 strain, 16) are regarded as superior asymmetric hydrogentransfer biocatalysts with which to produce (S)-alcohols.…”
mentioning
confidence: 99%